1983
DOI: 10.1002/marc.1983.030041206
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity of polyelectrolyte solutions containing mono‐and divalent counterions

Abstract: The activity and mobility of the counterions in strong polyelectrolyte solutions are considerably smaller than in simple electrolyte solutions of the same concentration in basemol dm-3, a fraction of the counterions being apparently bound to the highly charged polyions l). The theoretical studies of polyelectrolyte solutions containing a mixture of mono-and divalent counterions2-4) give rise to the conclusion that the fraction of bound counterions is higher for divalent counterions, and that the extent of bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…The single-chain cell model gives a larger slope at higher concentrations than the corresponding simulation of 8 chains in a periodic box for a 16mer, but the two simulation approaches give more or less the same result for a 256mer, which is beyond the long-chain limit of the simulations (see Section 3.5). Considering this limit, our simulations can be said to confirm the general conclusion that simulations give higher values of the osmotic coefficient than experiments, 6,10,12,16 as discussed in the Introduction.…”
Section: Comparison To Experimentssupporting
confidence: 79%
See 2 more Smart Citations
“…The single-chain cell model gives a larger slope at higher concentrations than the corresponding simulation of 8 chains in a periodic box for a 16mer, but the two simulation approaches give more or less the same result for a 256mer, which is beyond the long-chain limit of the simulations (see Section 3.5). Considering this limit, our simulations can be said to confirm the general conclusion that simulations give higher values of the osmotic coefficient than experiments, 6,10,12,16 as discussed in the Introduction.…”
Section: Comparison To Experimentssupporting
confidence: 79%
“…19 Comparisons to experimental values have been made for simulations of stiff chains and a general trend is that the simulations give higher values of the osmotic coefficient. 6,10,12,16 The difference is not always large and can sometimes be removed by adjusting the simulation parameters, 12 but Antypov and Holm got significantly higher values, which could not be explained by any known deficiency of the model. 16 Arh et al showed that for various experimentally measured polyelectrolytes, the osmotic coefficient does not approach 1 as the linear charge density goes to zero; i.e., there is a contribution to the non-ideality that is not due to electrostatic interactions.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, most of experimental work has been carried out at concentrations too high to be considered highly diluted, 29,30,36,37,42,45,47,48 hence preventing rigorous model discrimination. Furthermore, the water quality often did not correspond to that required for salt-free conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, often the disagreement between experiment and theory results from the fact that the experimental conditions were incompatible with assumptions from theoretical considerations. For example, the concentration region was far from being highly diluted [I1 -181, the water quality did not correspond to "salt free" conditions [13,[18][19][20][21], the samples had high polydispersity with parts of relatively short chains [21, 221, respectively. In principle, the strong increase of the equivalent conductivity and the maximum which was experimentally found in some cases at high dilution [19, 231 are not predicted by the existing theories.…”
mentioning
confidence: 99%